Classification of Partial Discharge Detection Technique in High Voltage Power Component: A Review - Rohani, M. N. K. H.; Zaidi, A. A. H.; Sakanovic, A.; Wooi, C. L.; Rosmi, A. S.; Isa, M.; Ismail, B. (International Journal of Integrated Engineering, 2019)
In this study, a review on categorization of partial discharge (PD) detection technique is presented. The PD detection is important in order to monitor and diagnosis the insulation health on high voltage (HV) power component. PD at high voltage transformer occurs due to the unscheduled maintenance, aging of equipment, breakdown of insulation, gas bubbles in insulation liquid, manufacturing error and etc. In order to maintain constant and high as possible of the transformer performance, it is essential to control, detect and measure the PD phenomena. There are many methods have been developed based on point of observation; optical, chemical, acoustic and electrical. However, the different methods have their own advantages and disadvantages.